Nutritional modulation of hepatic lipid metabolism in health and disease - Johnston, Richard David (2012)
The objective of this thesis was to assess the impact of altering macronutrient intakes on hepatic lipid metabolism. Two separate studies were performed, with liver triglyceride content being the principal outcome of both. In the first study 32 healthy and centrally overweight males were randomised to 2 periods, each of 2 weeks, of either a high fructose or glucose intake in a non-crossover fashion. Isoenergetic status was maintained by providing foodstuffs during the first period, followed by a 6 week washout and then a second period of ad libitum overfeeding. In the second study 55 patients with biopsy proven non-alcoholic fatty liver disease were randomised to 3 months 5g a day of capsules containing either n-3 polyunsaturated fatty acid or oleic enriched sunflower oil.